Rapid Standardized CT-Based Method to Determine Lean Body Mass SUV for PET—A Significant Improvement Over Prediction Equations - Riauka, Terence A.; Baracos, Vickie E.; Reif, Rebecca; Juengling, Freimut D.; Robinson, Don M.; Wieler, Marguerite; McEwan, Alexander J. B. (Frontiers in Oncology, 2022)
In 18F-FDG Positron Emission Tomography (PET) studies, maximum standardized uptake value (SUVmax) is the parameter commonly used to provide a measurement of the metabolic activity of a tumor. SUV normalized by body mass is affected by the proportions of body fat and lean tissue, which present high variability in patients with cancer. SUV corrected by lean body mass (LBM), denoted as SUL, is recommended to provide more accurate, consistent and reproducible SUV results; however LBM is frequently estimated rather than measured. Given the increasing importance of a quantitative PET parameter, especially when comparing PET studies over time to evaluate disease response clinically, and in oncological clinical trials, we set out to evaluate the commonly used equations originally derived by James (1976) and Janmahasatian (2005) against computerized tomography (CT)-derived measures of LBM. Methods: Whole-body 18F-FDG PET images of 195 adult patients with cancer were analyzed retrospectively. Representative liver SUVmean was normalized by total body mass, SUL was calculated using a quantitative determination of lean body mass based on the CT component of the PET/CT study (LBMCT) and compared against equation estimated SUL. Bland and Altman plots were generated for SUV-SUL differences. Results: This consecutive sample of patients undergoing usual care (male n=96; female n=99) varied in body mass (38-127 kg) and in BMI (14.7-47.2 kg/m2). LBMCT weakly correlated with body mass ((male r2=0.321; female r2=0.221) and thus SUV and SULCT were also weakly correlated ((male r2=0.243; female r2=0.114). Equations proved inadequate for the assessment of LBM. LBM estimated by James’ equation showed a mean bias (overestimation of LBM compared with LBMCT) in males (+6.13 kg; 95%CI 4.61-7.65) and in females (+6.32 kg; 95%CI 5.26-7.39). Janmahasatian’s equation provided similarly poor performance. Conclusions: CT-based LBM determinations incorporate the patient’s current body composition at the time of a PET/CT study, and the information garnered can provide care teams with information with which to more accurately determine FDG uptake values, allowing comparability over multiple scans and treatment courses and will provide a robust basis for the use of PERCIST in clinical trials.